Disability discrimination in children's sport. (June 2017) - Pearce, Simone
This article examines how the Disability Discrimination Act 1992 (Cth) relates to children's sport. More specifically, this article asks: how does the Disability Discrimination Act 1992 (Cth) address the treatment of children with disabilities participating in competitive sport? This article asserts that the 'attitude' in and around the construction of sport is framed in the ableism perspective that assumes ability. While there are specific disability sports, with rules designed to accommodate the different attributes people may possess, this article focuses on the nature and quality of access to, and experience in, sport that is not disability specific (mainstream sport), and argues that the law fails to protect children with disability being treated in a way that places them at a disadvantage. The primary concern raised by this article is that children with disability are not provided with fairness in competitive sport. This may be discriminatory.